INADEQUATE REGULATION OF PERSONAL IDENTITY. VIOLATION OF SELF-DETERMINATION RIGHT? - Gete Alonso, Maria Carmen (Unoesc International Legal Seminar, 2017)
The dignity of the person, their protection and respect, is a fundamental principle on which the positive legal systems of the western area, expressed in universal, international and domestic texts are based.